Qualifizierung des kyrogenen Mahlens zur Herstellung von gefüllten Kunststoffpulvern für das Lasersinterverfahren (Studienarbeit) - Wiebe, Robert

Polystyrol Nanopartikel asl alternative Fließhilfsmittel für SLS Materialien (Studienarbeit) - Aissani, Soufiane

Der Einfluss verschiedener Partikelgrößenfraktionen eines PA12 Pulvers auf den Lasersinterprozess und auf die resultierenden Bauteileigenschaften - Middelmann, Steffen

Untersuchung und Modellierung der Materialeigenschaften von lasergesintertem Polyamid 11 Pulver mit eincompoundierten Carbonfasern - Schröder, Dominik

Schmelze-Temperatur-Messung im Lasersinter-Prozess und Korrelation zu temperaturabhängigen Schmelzviskositäten - Baaske, Benno

Numerical Investigations on the Flow Field and the Transfer Function of a Centrifugal-DMA - Gröne, Sebastian

Konstruktion einer Vorrichtung zur Probenherstellung für das Sentmanat-Dehnrheometer - Otto, Moritz

Entwicklung einer Datenbank hergestellter Nanomaterialien mittel Gasphasensynthese (Studienarbeit) - Reimer, Jens

Materialqualifizierung und Nachhaltigkeitsanalyse eines biobasierten Polyamid 11-Pulvers für das selektive Lasersintern - Schulenkorf, Steffen

Entwicklung eines Verfahrens zur Probeentnahme aus einem Pulverkuchen im SLS-Prozess - Bürckner, Lorena Marie

Studie zum Auftragsverhalten von SLS-Pulvern in Abhängigkeit ihrer Fließfähigkeit - Engemann, Julian

Untersuchungen zum Einfluss der Pulverkonzentration auf den dynamischenmechanischen Partikelverrundungsprozess (Studienarbeit) - Hormatallah, Mouhssine; Ponusamy, SathishKumar

Leistungsbedarf beim dynamisch - mechanischen Partikelverrundungsprozess (Studienarbeit) - Tappe, Daniel; Ponusamy, SathishKumar

Polymorphic uncertainty in constitutive modeling of polymer composites at different scales - Penner, Eduard

Manufacturing-Morphology-Property Relationships for Rotating Shaft Sealing Systems - Thielen, Stefan; Antonyuk, Sergiy; Aurich, Jan C.; Beck, Tilmann; Hasse, Hans; Kopnarski, Michael; Magyar, Balázs; Sauer, Bernd; Smaga, Marek (Component Surfaces)

Measurement, Modelling, and Appli cation of Lubricant Properties at Extreme Pressures - Wingertszahn, Patrick; Schmitt, Sebastian; Thielen, Stefan; Oehler, Manuel; Magyar, Balázs; Koch, Oliver; Hasse, Hans; Stephan, Simon (Tribologie und Schmierungstechnik)
Lubricants play a central role in many technical applications, e.g. in bearings and gears as well as in machining processes. In such applications, lubricants are exposed to extreme conditions in the contact area. In lubrication gaps, the pressure can reach values up to 5 GPa. The thermophysical properties of lubricants, and in particular the viscosity, at such extreme conditions have an important influence on the friction and wear behavior of a tribosystem. Accordingly, reliable lubricant property models are a prerequisite for accurate tribological simulations, e.g. elastohydrodynamic lubrication (EHL) simulations. Presently, the vast majority of experimental thermophysical property data are only available up to 1 GPa. Thus, reliable and robust models with strong extrapolation capabilities to higher pressure are required. In this work, viscosity measurements of squalane in a temperature range be tween 20 °C and 100 °C and pressures up to 1 GPa were carried out. Based on that data, a physical model for the viscosity was developed. The model is built by combining a molecular-based equation of state with the so-called entropy scaling approach. Finally, we demonstrate how this fluid property model can be favorably integrated in an EHL simulation by an application programming interface (API). The novel hybrid modeling approach is promising for future applications.
Keywords: Surfaces; Coatings and Films; Surfaces and Interfaces; Mechanical Engineering; Mechanics of Materials

Evaluation of Usability Criteria Addressed by Static Analysis Tools on a Large Scale - Nachtigall, Marcus; Schlichtig, Michael; Bodden, Eric (Software Engineering 2023)
Static analysis tools support developers in detecting potential coding issues, such as bugs or vulnerabilities. Research emphasizes technical challenges of such tools but also mentions severe usability shortcomings. These shortcomings hinder the adoption of static analysis tools, and user dissatisfaction may even lead to tool abandonment. To comprehensively assess the state of the art, we present the first systematic usability evaluation of a wide range of static analysis tools. We derived a set of 36 relevant criteria from the literature and used them to evaluate a total of 46 static analysis tools complying with our inclusion and exclusion criteria - a representative set of mainly non-proprietary tools. The evaluation against the usability criteria in a multiple-raters approach shows that two thirds of the considered tools off er poor warning messages, while about three-quarters provide hardly any fix support. Furthermore, the integration of user knowledge is strongly neglected, which could be used for instance, to improve handling of false positives. Finally, issues regarding workflow integration and specialized user interfaces are revealed. These findings should prove useful in guiding and focusing further research and development in user experience for static code analyses.
Keywords: Automated static analysis; Software usability

Introducing FUM: A Framework for API Usage Constraint and Misuse Classification - Schlichtig, Michael; Sassalla, Steffen; Narasimhan, Krishna; Bodden, Eric (Software Engineering 2023)
Application Programming Interfaces (APIs) are the primary mechanism developers use to obtain access to third-party algorithms and services. Unfortunately, APIs can be misused, which can have catastrophic consequences, especially if the APIs provide security-critical functionalities like cryptography. Understanding what API misuses are, and how they are caused, is important to prevent them, eg, with API misuse detectors. However, definitions for API misuses and related terms in literature vary. This paper presents a systematic literature review to clarify these terms and introduces FUM, a novel Framework for API Usage constraint and Misuse classification. The literature review revealed that API misuses are violations of API usage constraints. To address this, we provide unified definitions and use them to derive FUM. To assess the extent to which FUM aids in determining and guiding the improvement of an API misuses detector’s capabilities, we performed a case study on the state-of the-art misuse detection tool CogniCrypt. The study showed that FUM can be used to properly assess CogniCrypt’s capabilities, identify weaknesses and assist in deriving mitigations and improvements.
Keywords: API misuses API usage constraints; classification framework; API misuse detection; static analysis

Approximate simulation of the hysteresis friction of radial shaft seals - Bührmann, Tobias; Magyar, Balázs (Tribologie und Schmierungstechnik)

Ergebnisse des UneS-Projektes und mögliche Handlungsempfehlungen für die Unterstützung von chancengerechten digitalisierungsbezogenen Schulentwicklungsprozessen durch Schulträger - Drossel, Kerstin; Bette, Ricarda; Oldak, Anna; Eickelmann, Birgit

Ergebnisse des UneS-Projektes und mögliche Handlungsempfehlungen für chancengerechte digitalisierungsbezogene Schulentwicklungsprozesse auf Einzelschulebene - Drossel, Kerstin; Oldak, Anna; Bette, Ricarda; Eickelmann, Birgit

Prozesskettenorientierte Herstellbarkeitsanalyse von Produkten durch die Nutzung eines Constraint-Satisfaction-Problems - Herrmann, Kevin; Pusch, Felix; Plappert, Stefan; Bode, Behrend; Mozgova, Iryna; Gembarski, Paul Christoph; Lachmayer, Roland (Stuttgarter Symposium für Produktentwicklung SSP 2023: Tagungsband zur Konferenz)
Dieser Beitrag stellt eine rechnergestützte Modellierungsstrategie vor, um Prozesskettenwissen, wie die Gestaltung der Fertigungsstufen, prozessübergreifende Fertigungsrestriktionen oder Fertigungshilfsmittel, für die Produktgestaltung zu formalisieren und im Kontext des Design for Manufacturing für Produkt- und Prozessgestaltungsentscheidungen bereitzustellen. Dabei werden am Beispiel einer Tailored-Forming-Prozesskette die Herstellungsschritte einer Multimaterial-Welle mittels eines Constraint-Satisfaction-Problems (CSP) modelliert, indem die geometrischen Transformationen einzelner Fertigungsstufen sowie Fertigungsrestriktionen in Form von Constraints und Fertigungsstufen sowie Fertigungshilfsmittel über Parameter in den CSP-Variablen formuliert werden. Das CSP ist damit in der Lage, ausgehend von einem Geometriemodell eines Bauteils eine prozesskettenorientierte Restriktionsprüfung zur Herstellbarkeitsbewertung durchzuführen und automatisiert Fertigungsstufen sowie Fertigungshilfsmittel zu konfigurieren.

ENHANCED FINDABILITY AND REUSABILITY OF ENGINEERING DATA BY CONTEXTUAL METADATA - Altun, Osman; Oladazimi, Pooya; Wawer, Max Leo; Raumel, Selina; Wurz, Marc; Barienti, Khemais; Nürnberger, Florian; Lachmayer, Roland; Mozgova, Iryna; Koepler, Oliver; Auer, Sören (Proceedings of the Design Society)
Abstract Complex research problems are increasingly addressed by interdisciplinary, collaborate research projects generating large amounts of heterogeneous amounts of data. The overarching processing, analysis and availability of data are critical success factors for these research efforts. Data repositories enable long term availability of such data for the scientific community. The findability and therefore reusability strongly builds on comprehensive annotations of datasets stored in repositories. Often generic metadata schema are used to annotate data. In this publication we describe the implementation of discipline specific metadata into a data repository to provide more contextual information about data. To avoid extra workload for researchers to provide such metadata a workflow with standardised data templates for automated metadata extraction during the ingest process has been developed. The enriched metadata are in the following used in the development of two repository plugins for data comparison and data visualisation. The added values of discipline-specific annotations and derived search features to support matching and reusable data is then demonstrated by use cases of two Collaborative Research Centres (CRC 1368 and CRC 1153).

Datenqualitätssicherung im Forschungsprozess am Beispiel von Zugversuchen - Müller, Laura; Wawer, Max Leo; Heimes, Norman; Uhe, Johanna; Koepler, Oliver; Auer, Sören; Lachmayer, Roland; Mozgova, Iryna (DS 125: Proceedings of the 34th Symposium Design for X (DFX2023))
Progressive digitization throughout the entire product data life cycle requires a more sensitive handling and understanding of data within engineering processes. Regarding engineering research data, the aim is to implement the FAIR data principles (Findable, Accessible, Interoperable, Reusable) to guarantee the post-usability of research data. To ensure the quality of data throughout the entire research process a methodical approach had been developed. Based on the quality categories Intrinsic, Representative, Contextual and Available, the related quality dimensions are considered differentiated along the research data life cycle and presented in a concept. As a use case, this concept is carried out on a tensile test with documentation of results in a research data management system.

Approach for a Safety Element out of Context for an Actuator Circuit Control Module - Noun, H.; Mozgova, Iryna; Abdelfattah, M.; Zeller, G.; Rajesh, G.; Lachmayer, R. (International Journal of Industrial and Manufacturing Engineering)
Several modules in automotive are usually modified and adapted for various project-specific applications. Due to a standardized safety concept a high reusability is accessible. A safety element out of context (SEooC) according to ISO 26262 can be a suitable approach. Based on the same safety concept and analysis, common modules can reach high reusability. For developing according to a module out of context, an appropriate and detailed development approach is required. This paper shows how to deduce this development processes for platform modules. Therefore, the detailed approach of the SEooC is derived. The aim is to create a detailed workflow for all phases of the development and integration of any kind of system modules. As an application example, an automotive project for an actuator control module is considered.

Numerical Investigation of the Coupled Friction Behavior in the Clinching Process Chain - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

HenDi-Data (data package) v2.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

HenDi-Data (data package) v1.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

Ersatzmodellentwicklung zur Berücksichtigung der lokalen Fügeelementkinematik in mechanisch gefügten Verbindungen für die Bauteilauslegung im stahlintensiven Karosseriebau - Bähr, Philipp; Striewe, Marius; Meschut, Gerson; Sommer, Silke; Hein, David (13. Kolloquium: Gemeinsame Forschung in der Mechanischen Fügetechnik)

Methode zur Simulation des temperaturabhängigen Crashverhaltens von strukturellen Klebverbindungen - Striewe, Marius; Teutenberg, Dominik; Hein, David; Meschut, Gerson; Schmelzle, Lars; Mergheim, Julia; Possart, Gunnar (Klebtechnische Doktorandenseminare 2020 - 2022)

proDruck 3D-Druck – Technologie der Industrie 4.0 – als Mittel der Inklusion für Menschen mit Behinderungen in die Arbeitswelt - Kruse, Anne; Müller, Laura; Ott, Manuel; Koch, Rainer; Hügel, Joachim; Finke, Florian; Winter, Stephan; Gust, Thomas (Personennahe Dienstleistungen der Zukunft)

3D-Druck – Eine Technologie als Schlüssel zur Steigerung der Teilhabe - Kruse, Anne; Müller, Laura; Ott, Manuel; Jung, Philipp; Koch, Rainer; Hügel, Joachim; Finke, Florian; Winter, Stephan; Gust, Thomas (Personennahe Dienstleistungen der Zukunft)

When High‐Temperature Cesium Chemistry Meets Self‐Templating: Metal Acetates as Building Blocks of Unusual Highly Porous Carbons - Li, Jiaxin; Kossmann, Janina; Zeng, Ke; Zhang, Kun; Wang, Bingjie; Weinberger, Christian; Antonietti, Markus; Odziomek, Mateusz; López‐Salas, Nieves (Angewandte Chemie International Edition)
Self-templating is a facile strategy for synthesizing porous carbons by direct pyrolysis of organic metal salts. However, the method typically suffers from low yields (<4%) and limited specific surface areas (SSA<2000 m2 g−1) originating from low activity of metal cations (e.g., K+ or Na+) in promoting construction and activation of carbon frameworks. Here we use cesium acetate as the only precursor of oxo-carbons with large SSA of the order of 3000 m2 g−1, pore volume approaching 2 cm3 g−1, tunable oxygen contents, and yields of up to 15 %. We unravel the role of Cs+ as an efficient promoter of framework formation, templating and etching agent, while acetates act as carbon/oxygen sources of carbonaceous frameworks. The oxo-carbons show record-high CO2 uptake of 8.71 mmol g−1 and an ultimate specific capacitance of 313 F g−1 in the supercapacitor. This study helps to understand and rationally tailor the materials design by a still rare organic solid-state chemistry.
Keywords: CO2 Adsorption; Cesium Acetate; Cesium Effect; Porous Carbons; Supercapacitor

TPACK, DPACK, XY-Pack? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas; Jenert, Tobias (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Das TPACK-Modell wird häufig zur Konzeptualisierung digitaler Kompetenzen in der Lehrer:innenbildung herangezogen. Es stellt die Bezüge des Lehrer:innenwissens zwischen den Dimensionen des inhaltlichen, pädagogischen und technologischen Wissens her. Wir analysieren in diesem Beitrag die Passung von TPACK zur Modellierung digitaler Kompetenzen für den Kontext der beruflichen Bildung, insb. mit Blick auf die Inhaltsdimension. Wir argumentieren, dass TPACK und solche Modelle, die sich daran anlehnen, den doppelten inhaltlichen Gegenstandsbezug der beruflichen Bildung nicht hinreichend abbilden. Darauf aufbauend diskutieren wir mögliche Weiterentwicklungen des Modells für die berufliche Bildung sowie dessen Bedeutung für die berufliche Lehrer:innenbildung.

Evidenzbasierte Hochschuldidaktik - Scharlau, Ingrid; Jenert, Tobias (Hochschuldidaktik als Wissenschaft: Disziplinäre, interdisziplinäre und transdisziplinäre Perspektiven)

TPACK, DPACK, XY-PACK? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas

Der Einsatz von didaktischen Fallstudien zur Erkundung digital transformierter Arbeits- und Geschäftsprozesse im Studienfach Wirtschaftswissenschaft für das Lehramt an Berufskollegs - Sänger, Niklas

Didaktische Fallstudien zur exemplarischen Erkundung der digitalen Transformation der Arbeits- und Geschäftsprozesse im Studienfach Wirtschaftswissenschaft für das Lehramt an Berufskollegs - Sänger, Niklas

Technological Pedagogical Content Framework for the Vocational Teacher Education in Germany - Sänger, Niklas

Vorstellung eines Trainings zur Förderung des selbstregulierten unternehmerischen Lernens in der Entrepreneurship-Education. - Büker, Ronja; Jenert, Tobias; Fahrbach, Manuel (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)

TPACK, DPACK, XY-PACK? Eine kritische Auseinandersetzung mit der Modellierung digitaler Inhaltskompetenzen für die berufliche Bildung - Sänger, Niklas; Jenert, Tobias; Kremer, H.-Hugo (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)

Integrationsgestaltung ausbildungsintegrierender Studienprogramme. Eine theorie- und fallstudienbasierte Analyse - Jenert, Tobias; Mordhorst, Lisa Friederike Anna (Jahrestagung der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft)

Integrationsgestaltung ausbildungsintegrierender Studienprogramme. Eine theorie- und fallstudienbasierte Analyse - Mordhorst, Lisa Friederike Anna; Jenert, Tobias (Jahrestagung der Gesellschaft für Hochschulforschung)

Jenert, T. & Büker, R. (2023). Designing Self-Regulation interventions for different target groups in Entrepreneurship Education - Jenert, Tobias; Büker, Ronja

Deep neural networks on diffeomorphism groups for optimal shape reparametrization - Celledoni, Elena; Glöckner, Helge; Riseth, Jørgen; Schmeding, Alexander (BIT Numerical Mathematics)

Aspects of control theory on infinite-dimensional Lie groups and G-manifolds - Glöckner, Helge; Hilgert, Joachim (Journal of Differential Equations)
Keywords: 22E65; 28B05; 34A12; 34H05; 46E30; 46E40

Diffeomorphism groups of convex polytopes - Glöckner, Helge (Journal of Convex Analysis)
Let $E$ be a finite-dimensional real vector space and $M\subseteq E$ be a convex polytope with non-empty interior. We turn the group of all $C^∞$-diffeomorphisms of $M$ into a regular Lie group.

Mapping groups associated with real-valued function spaces and direct limits of Sobolev-Lie groups - Glöckner, Helge; Tárrega, Luis (Journal of Lie Theory)

Workload-Aware Periodic Interconnect BIST - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Design &Test)
System-level interconnects provide the backbone for increasingly complex systems on a chip. Their vulnerability to electromigration and crosstalk can lead to serious reliability and safety issues during the system lifetime. This article presents an approach for periodic in-system testing which maintains a reliability profile to detect potential problems before they actually cause a failure. Relying on a common infrastructure for EM-aware system workload management and test, it minimizes the stress induced by the test itself and contributes to the self-healing of system-induced electromigration degradations.
Keywords: Electrical and Electronic Engineering; Hardware and Architecture; Software

Robust Pattern Generation for Small Delay Faults under Process Variations - Jafarzadeh, Hanieh; Klemme, Florian; Reimer, Jan Dennis; Najafi Haghi, Zahra Paria; Amrouch, Hussam; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE International Test Conference (ITC'23), Anaheim, USA, October 2023)

Simplified numerical calculation of the isothermal, three-dimensional, Non-Newtonian flow characteristics of single-screw melt-extruder - Stüker, Daniel; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Introduction—The Digital Twin of Humans - Gräßler, Iris; Steffen, Eckhard; Maier, Günter W.; Roesmann, Daniel (The Digital Twin of Humans)

The Digital Twin of Humans

Calibration of a Contact Model for DEM Simulations of Grooved Feed Sections of Single Screw Extruders - Schöppner, Volker; Brüning, Florian (36th International Conference of the Polymer Processing Society (PPS-36))

Individual Assembly Guidance - Pöhler, Alexander; Gräßler, Iris (The Digital Twin of Humans)

The short-and long-term properties of welded high-temperature-resistant thermoplastics - Vogtschmidt, Sascha; Schöppner, Volker

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Analysis and modelling of the material degradation of polypropylene on the co-rotating twin-screw extruder - Altepeter, Matthias; Wanke, Sven; Schöppner, Volker (INTERNATIONAL CONFERENCE ON HUMANS AND TECHNOLOGY: A HOLISTIC AND SYMBIOTIC APPROACH TO SUSTAINABLE DEVELOPMENT: ICHT 2022)

Integration of Human Factors for Assembly Systems of the Future - Roesmann, Daniel; Gräßler, Iris (The Digital Twin of Humans)

Conceptions and Feasibility Study of Fiber Orientation in the Melt as Part of a Completely Circular Recycling Concept for Fiber-Reinforced Thermoplastics - Moritzer, Elmar; Tölle, Lisa; Greb, C.; Haag, M. (Journal of Composites Science)

Polypropylene Degradation on Co-Rotating Twin-Screw Extruders - Schöppner, Volker; Altepeter, Matthias; Austermeier, Laura; Wanke, Sven; Meinheit, Philipp (Polymers 2023)

Investigation of the Homogenization Performance of Various Faceted Mixers and Optimization with Regard to Mixing as well as Pressure Throughput Behavior - Schöppner, Volker; Frank, Maximilian

Design of a test bench for measuring the degradation behavior of plastics during processing - Schall, Christoph Wilhelm Theodor; Schöppner, Volker (PPS36)
Keywords: Computing Resources Provided by the Paderborn Center for Parallel Computing

Material Characterization of Polypropylene and Polystyrene Regarding Molecular Degradation Behavior - Schöppner, Volker; Schall, Christoph Wilhelm Theodor (Materials)

Characterization of additively manufactured parts for direct screwing - Moritzer, Elmar; Held, Christian (Welding in the World)

POTENTIALS AND GOALS OF MODELS IN STRATEGIC PRODUCT PLANNING AND INNOVATION MANAGEMENT - Gräßler, Iris; Koch, Anna-Sophie; Tusek, Alena Marie (Proceedings of the Design Society)
Abstract New trends and technologies in product creation increase complexity, but at the same time create new potentials such as efficiency rise in task processing by Artificial Intelligence. Established models in the early phase of product creation such as the W-model or the Aachener Innovation Management model, do not fully exploit these new potentials in the field of strategic product planning and innovation management (SPPIM). For this reason, existing models are analysed in SPPIM in order to derive a requirements profile consisting of potentials and goals for a new model. A new model in SPPIM lays the foundation to support companies in enabling a more efficient task fulfilment by taking advantage of new technologies and trends. To guide the development of advanced SPPIM models, the derived potentials and goals are applied to the guideline VDI 2220:1980.

Interdependency study of design guidelines - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)

Sustainable product life cycle - Hesse, Philipp; Gräßler, Iris (Climate Protection, Resource Efficiency, and Sustainable Engineering: Transdisciplinary Approaches to Design and Manufacturing technology.)

Begriffe der strategischen Produktplanung und -entwicklung. Produkt und hybride Leistung - Gräßler, Iris; Ovtcharova, Jivka; Dattner, Michael; Dietert, Tilko; Dietz, Patrick; Elstermann, Matthes; Fayet, Celestin; Hauck, Andreas; Häuser, Frank; Fischer, Holger; Herzog, Michael; Köhler, Christian; et al.

Post-pandemic online mathematics and statistics support: Practitioners’ opinions in Germany and Great Britain & Ireland - Gilbert, H.; Schürmann, M.; Liebendörfer, M.; Lawson, D.; Hodds, M. (International Journal of Mathematical Education in Science and Technology)
Keywords: Applied Mathematics; Education; Mathematics (miscellaneous)

Fachdidaktisches Design von Begründungsvideos im Projekt studiVEMINTvideos - Biehler, Rolf; Guntermann, Dominik; Liebendörfer, Michael; Krämer, Sandra; Schlüter, Sarah (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Erfassung und Vergleich (mathematischer) Eingangsvoraussetzungen angehender Studierender verschiedener mathematikhaltiger Studiengänge - Göller, Robin; Gildehaus, Lara; Liebendörfer, Michael; Besser, Michael (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2021. Beiträge zum gleichnamigen Online-Symposium am 12 November 2021 aus Bochum)

Zu digital - zu viel - zu schwer? Qualitative Einsichten in das Erleben und Handeln von Erstsemester-Studierenden der Mathematik während der Corona-Pandemie - Kempen, Leander; Liebendörfer, Michael (Hanse-Kolloquium zur Hochschuldidaktik der Mathematik 2021. Beiträge zum gleichnamigen Online-Symposium am 12 November 2021 aus Bochum)

Bearbeitungsmuster von Studierenden im Umgang mit formalen Definitionen im Kontext konstanter Folgen - Schlüter, Sarah; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Förderung prozeduraler Flexibilität durch Lernvideos mit interaktiven Aufgaben - Krämer, Sandra; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Preservice teachers’ mathematics-related values and expectancy in the transition from school to university
Many preservice mathematics teachers lose their motivation during their first year at university. This phenomenon has been repeatedly described in recent years but is not yet fully understood. Since motivation may relate to different objects such as mathematics or teaching, we aim to qualitatively reconstruct different facets of the central motivational constructs of Situated-Expectancy-Value theory (intrinsic value, attainment value, utility value, cost, and expectancy of success) for preservice mathematics teachers. The analysis of longitudinal group interviews of 14 preservice higher-secondary mathematic teachers from a German university revealed different objects of motivation (e.g., teaching mathematics, scientific mathematics, procedural mathematics, or proof-based mathematics) in preservice teachers' values and expectancy of success. Furthermore, relations between those values and expectancy of success were identified that played a significant role in preservice teachers’ motivational development over their first semester (e.g., relations of attainment value for scientific mathematics and psychological cost). Theoretical and practical implications towards a teaching-specific conceptualization of expectancy of success and values and value interventions are being discussed.

Approach for a sustainable process chain in manufacturing of fasteners for mechanical joining - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson

Determination of Correlations between Melt Quality and the Screw Performance Index in the Extrusion Process - Trienens, Dorte; Schöppner, Volker; Bunse, Robin (Polymers 2023)

Improvement of a method for the correction of wall slip effects within the rheological measurements of filled rubber compounds - Schöppner, Volker; Kleinschmidt, Dennis (SPE Polymers)

Creating Synthetic Training Data for Machine Vision Quality Gates - Gräßler, Iris; Hieb, Michael; Roesmann, Daniel; Unverzagt, Marc

Dynamic conformity assessment for joining force monitoring using Bayes filters - Butzhammer, Lorenz; Kappe, Fabian; Meschut, Gerson; Hausotte, Tino (Materials Research Proceedings)
Monitoring force-displacement or force-time curves is a widely used quality control technique in the field of mechanical joining. For online monitoring of self-piercing riveting, envelope curves are often used to define a tolerance zone for the measured setting force. However, the measurement uncertainty is typically not considered and the force curve of a joint can be wrongly rated as non-conform due to measurement errors and noise. In this article, we present a method for dynamical online filtering and uncertainty determination for noisy force curves using two types of Bayesian filters. The methodology is based on a Bayesian probability framework using a priori information for the process curve and sensor noise. To investigate the general feasibility of the method, force measurements with different noise levels are simulated and processed. The conformity is further assessed taking the uncertainty of the filtered signal into account. The results show that the Bayes filter technique is principally able to reduce noise for well-known characteristics of the process curve and sensor noise. Advantages over common filtering techniques, especially for experimental conditions with less known characteristics, are still to be verified. The methodology could be used in future for closed-loop controls to adapt process parameters dynamically.

Creating Synthetic Datasets for Deep Learning used in Machine Vision - Gräßler, Iris; Hieb, Michael

CONSIDERING ENGINEERING ACTIVITIES AND PRODUCT CHARACTERISTICS TO ACHIEVE MATERIAL CIRCULARITY BY DESIGN - Gräßler, Iris; Hesse, Philipp (Proceedings of the Design Society)
Abstract To select design guidelines engineers have to identify relevant from a bewildering amount of design guidelines. In this paper, a rule-based method for selecting design guidelines for material circularity selection is presented. For this purpose, a generic Product Life Cycle model is detailed with regard to Multi Material cycles (gPLC-MM). The presented method is divided into four steps. Core of the presented method is the comparison of circular product strategies with product life phases and material recovery processes. Engineering activities and increments of the product architecture are used to identify design guidelines. The results show that through the material circularity-oriented design guideline identification method, the product architecture is designed for different processes and technologies, to recover materials. The method allows engineers to select guidelines in a more targeted and consolidated way in sustainability-friendly product engineering.
Keywords: Sustainability; Circular economy; Conceptual design

Virtual Test Scenarios for Human-Centered Design with Virtual Measurement Systems - Gräßler, Iris; Roesmann, Daniel; Unverzagt, Marc; Pottebaum, Jens (Poster)
The involvement of human workers is an essential part of the design of production systems. In this context, test scenarios in Virtual Reality are increasingly used to verify the fulfillment of requirements. This paper proposes a procedure for generating virtual test scenarios. The objective is to support human- centered design by means of virtual measurement systems. The procedure involves three steps: selecting relevant human factors in requirements, modeling the virtual test scenario, and carrying out the verification study. The goal is to advance the significance of testing outputs.
Keywords: virtual reality; virtual measurement systems; virtual test scenario; human-centered design

Virtual learning environment for teaching the handling of collaborative robots - Gräßler, Iris; Hieb, Michael; Roesmann, Daniel; Unverzagt, Marc; Pottebaum, Jens (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Cloud-Computing für die Verwendung synthetischer Trainingsdaten für Machine Vision Quality Gates - Gräßler, Iris; Hieb, Michael (Automation 2023)

Wall Slip-Free Viscosity Determination of Filled Rubber Compounds Using Steady-State Shear Measurements - Brüning, Florian; Kleinschmidt, Dennis; Petzke, J. (Polymers)

Recycling-Ansatz für mehrkomponentige Kunststoffprodukte durch thermische Verbundtrennung - Schöppner, Volker; Austermeier, Laura; Brüning, Florian; Oldemeier, Jan Philipp; Brandt, O. (EXTRUSION)

Anvil-free ultrasonic welding for welding situations with one sided access - Schöppner, Volker; Arndt, Theresa (76th Annual Assembly of the International Institute of Welding (IIW))

Elastomerrecycling mittels Mikrowellenstrahlung - Brüning, Florian; Kleinschmidt, Dennis; Petzke, J. (Kunststoffland NRW Report)

Conformal Cooling at Low Cost - Moritzer, Elmar; Kartelmeyer, S.; Kringe, R.; Jaroschek, C. (Plastics Insights)

Creating Synthetic Training Datasets for Inspection in Machine Vision Quality Gates in Manufacturing - Gräßler, Iris; Hieb, Michael (Lectures)
Manufacturing companies face the challenge of reaching required quality standards. Using optical sensors and deep learning might help. However, training deep learning algorithms require large amounts of visual training data. Using domain randomization to generate synthetic image data can alleviate this bottleneck. This paper presents the application of synthetic image training data for optical quality inspections using visual sensor technology. The results show synthetically generated training data are appropriate for visual quality inspections.
Keywords: synthetic training data; machine vision quality gates; deep learning; automated inspection and quality control; production control

Efficient Formalisation of Technical Requirements for Generative Engineering - Gräßler, Iris; Preuß, Daniel; Brandt, Lukas; Mohr, Michael (Proceedings of the Design Society)

Combination of versatile self-piercing riveting processes - Wituschek, Simon; Kappe, Fabian; Meschut, Gerson; Lechner, Michael (Materials Research Proceedings)
Due to economic and ecological framework conditions, a resource-saving utilization of raw materials and energy is becoming increasingly important in particular in the mobility sector. For the reduction of moving masses and the resources consumed, lightweight construction technologies are part of modern production processes in vehicle manufacturing, for example in the form of multi-material systems. Challenging in the manufacture of multi-material systems especially in view of changing supply chains is the variety of materials and geometries that bring conventional joining processes to their limits. Therefore, new processes are required, which can react versatile to process and disturbance variables. A widely used industrial joining process is semi-tubular self-piercing riveting, which is however a rigid process. To increase the versatility, the two newly established processes multi-range self-piercing riveting and tumbling self-piercing riveting are combined and the capabilities for targeted material flow control are united. Therefore, an innovative two-stage process based on the combination is introduced in this paper. The rivet is set with the multi-range self-piercing riveting process with an overlap of the rivet head and then formed by a tumbling process. Further, a specific adaptation of the tumbling strategy is used to investigate the possibility of reducing cracks in the rivet head. Thereby, different tumbling strategies are used and similar geometric joint formations are achieved to compare the results.

Deciding Subsumption in Defeasible $$\mathcal {ELI}_\bot $$ with Typicality Models - de Camargo e Souza Câmara, Igor; Turhan, Anni-Yasmin (Logics in Artificial Intelligence)

Optimal Alignment of Temporal Knowledge Bases - Gil, Oliver Fernández; Patrizi, Fabio; Perelli, Giuseppe; Turhan, Anni-Yasmin (CoRR)

Advances In RTM Manufacturing Of Metal-FRP Hybrids By Self-Sealing And In-Mold Cleaning Techniques - Chalicheemalapalli Jayasankar, Deviprasad
The importance of fiber-reinforced plastics for lightweight construction applications is steadily increasing due to their outstanding weight-specific property values. However, a decisive disadvantage of these composite materials has so far been the high material and process costs, which is why fiber-reinforced plastics are almost exclusively used in small to medium-sized series. Optimization of manufacturing methods is of great importance to reduce the production cost. In this study, two concepts are proposed that can optimize vacuum assisted light resin transfer molding (VA-LRTM) further, leading to a possibility of fully automatic process. Conventional VA-LRTM methods are used to produce complex fiber-reinforced plastics (FRP) and hybrid components. Traditional molds used to produce components via VA-LRTM are sealed using polymer materials to prevent the leakage of matrix system. The seals undergo tremendous amounts of thermal, chemical, and mechanical loadings. Thus, sealings must be replaced in short intervals. In the current study, a concept where sealing is achieved by accelerating the curing of matrix system itself with the help of heating elements and catalysts resulting in a self-sealing approach is proposed. Another concern is mold surface contamination during component production. To address this, a modified automatic cleaning technique based on ultrasonic cleaning was proposed which can be integrated into the production line with minimum modification. Both the proposed concepts were validated and optimized using experiments, simulations, and analytical approaches by producing metal-FRP hybrid shafts.
Keywords: fiber-reinforced plastics; resin transfer molding; composites

In-Mold Assembly of Hybrid GMT-Steel Brake Pedals by Compression Molding - Chalicheemalapalli Jayasankar, Deviprasad; Stallmeister, Tim; Lückenkötter, Julian; Tröster, Thomas
Keywords: Compression Molding; Glass Mat Thermoplastics; Hybrid Brake Pedal

Turning Disciplinary Differences from a Brake into a Motor in Higher Education (Collaboration) - Sloane, Hannah Sabrina; Schmöckel, Sabrina

On the Multimodal Resolution of a Search Sequence in Virtual Reality - Klowait, Nils (Human Behavior and Emerging Technologies)
In virtual reality (VR), participants may not always have hands, bodies, eyes, or even voices—using VR helmets and two controllers, participants control an avatar through virtual worlds that do not necessarily obey familiar laws of physics; moreover, the avatar’s bodily characteristics may not neatly match our bodies in the physical world. Despite these limitations and specificities, humans get things done through collaboration and the creative use of the environment. While multiuser interactive VR is attracting greater numbers of participants, there are currently few attempts to analyze the in situ interaction systematically. This paper proposes a video-analytic detail-oriented methodological framework for studying virtual reality interaction. Using multimodal conversation analysis, the paper investigates a nonverbal, embodied, two-person interaction: two players in a survival game strive to gesturally resolve a misunderstanding regarding an in-game mechanic—however, both of their microphones are turned off for the duration of play. The players’ inability to resort to complex language to resolve this issue results in a dense sequence of back-and-forth activity involving gestures, object manipulation, gaze, and body work. Most crucially, timing and modified repetitions of previously produced actions turn out to be the key to overcome both technical and communicative challenges. The paper analyzes these action sequences, demonstrates how they generate intended outcomes, and proposes a vocabulary to speak about these types of interaction more generally. The findings demonstrate the viability of multimodal analysis of VR interaction, shed light on unique challenges of analyzing interaction in virtual reality, and generate broader methodological insights about the study of nonverbal action.
Keywords: Human-Computer Interaction; General Social Sciences; Social Psychology; Virtual Reality : Multimodality; Nonverbal Interaction; Search Sequence; Gesture; Co-Operative Action; Goodwin; Ethnomethodology